A GENERALIZED MODEL OF THE GLOW DISCHARGE BASED ON THE TRIGONOMETRIC BASIS - АНДРІЄНКО, О. В. (Technologies and Engineering, 2024)
Purpose. To review and classify currently existing glow discharge models by the method of mathematical description of processes, pressure, gas type and electrode geometry. The article is aimed at creating a generalized model of the discharge, which will determine the influence of each parameter on the characteristics of the discharge. Methodology. To achieve the goals of the research, methods of theoretical analysis of scientific sources were used, as well as a mathematical method for describing a generalized discharge model based on an orthonormal basis, in particular a trigonometric basis. Findings. An overview of the glow discharge was conducted, a classification of models based on analytical methods in their basis was proposed. The vector of parameters common to all models is isolated. Also, during the analysis, a comparison of the characteristics of the models was carried out in the form of a table. A generalized model for the study of gas discharges by the method of modeling using orthonormal bases was proposed. As an example, the formation of a vector of variable parameters in the trigonometric basis is given. Originality. The article offers a generalized discharge model that demonstrates how a change in a specific parameter affects the discharge characteristics. Such a model allows you to simultaneously change the parameters of the model, accumulate reactions to changes in parameters in each test, and upon completion, based on the results of the analysis, isolate the effect of each parameter with a cumulative change in the parameters of the model. Practical value: The model allows analyzing the influence of various parameters on the discharge regardless of the specific conditions of the experiment. The use of an orthonormal basis for the representation of parameters makes it possible to identify which parameters have the greatest influence on the stability and efficiency of the discharge both individually and in combination with other parameters. This makes it possible to optimize these parameters to achieve the best results in specific conditions, making it a universal tool for researchers and engineers, which facilitates the analysis of the relationships between parameters and allows you to get a more complete picture of the system's behavior.